Literature Review: Hubungan Kejadian Sedentary Lifestyle dengan Obesitas di Masa Pandemi Covid-19 - Mochamad Zulfikar Assagaf; Syahrul Ramadhan; Septa Indra Puspikawati (Media Gizi Kesmas, 2023)
Background: During the Covid-19 pandemic, it caused various problems that affected human life. One of the influential problems is the pattern of life lived by humans. The decrease in physical activity encourages people to carry out sedentary lifestyle activities. Sedentary lifestyle is a lifestyle that doesn't move much outside of human sleep. Due to changing human lifestyles, this can increase the risk of weight gain and obesity in humans. Objectives: Knowing the relationship between sedentary events and obesity during the Covid-19 pandemic Methods: The research design is a literature review related to the incidence of sedentary lifestyle and obesity during the Covid-19 pandemic. The inclusion criteria are references from journal articles that are free access, in Indonesian, in the year of publication 2020-2022. In addition, using PICO which consists of the population, namely students and students in Indonesia, intervention, namely sedentary lifestyle, and Outcome, namely Obesity. While the exclusion criteria were not review articles, experimental studies, paid articles, and the year the article was published under 2020. Reference searches used the Google Scholar and Garuda journal search engines with the keywords "sedentary lifestyle", "sedentary lifestyle", and "obesity". Discussion: There were 5 articles (83.3%) that had a significant relationship between sedentary behavior and nutritional status and 1 article (16.7%) did not have a significant relationship between sedentary behavior and nutritional status. Conclusion: Sedentary factors related to the incidence of obesity are watching television, playing gadgets, sitting watching television and eating, sitting relaxed, sleeping by listening to music, and playing laptops